(untitled) (Bangladesh Journal of Botany, 2014)
Combining ability on grain yield and its components from line × tester analysis of 70 rice hybrids produced by crossing seven CMS lines and ten testers of local and exotic origin were studied. The analysis revealed higher sca variance than gca variance for all the traits indicating the prevalence of non-additive gene action. Testers played important role towards panicle length (48.18%), spikelet fertility (60.46%) and grain yield/plant (55.44%) indicating predominant of paternal influence for these traits. The contribution of interactions (line × tester) were found vital for plant height (58.55%), effective tillers/plant (51.69%), days to 50% flowering (48.95%), days to maturity (48.32%), flag leaf length (68.55%), panicles/m2 (48.61%) and panicle weight (50.39%). D.ShanA was the only good general combiner among the female parent for earliness and dwarfness. Male parent IR64R was best general combiner for dwarfness. The crosses BRRI9A × BR168R and D.ShanA × BR168R were identified as most promising for yield and desired traits based on sca effects, per se performance and gca effects of parents for grain yield and its components in rice which could be exploited beneficially in future rice breeding program by adopting heterosis breeding strategy. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18022 Bangladesh J. Bot. 42(2): 215-222, 2013 (December